2-Methoxyoestradiol Impairs Mouse Embryo Implantation Via F-Spondin - Cardenas-Sankan, G; Orihuela-Diaz, P; Godoy-Guzman, C; Diaz-Saldivar, P; Guajardo-Correa, E (CSIRO, 2019)
The anti-implantation effects of high oestradiol (E 2 ) concentrations could be mediated by E 2 metabolites. Herein, we examined whether 2-methoxyoestradiol (2ME) impairs embryo implantation via its target protein F-spondin. Mice on Day 3 of pregnancy were treated with E 2 concomitantly with the cathecol-O-methyl transferase inhibitor OR486 and the number of implanted embryos was recorded 5 days later. The effect of 2ME or 4-methoxyoestradiol (4ME) on embryo implantation was also investigated. Plasma and uterine levels of 2ME were measured 0.5, 1 or 3 h after E 2 treatment while the mRNA for spondin 1 (Spon1) and F-spondin were determined in the uterus 3, 6, 12 or 24 h after 2ME treatment. Finally, the effect of a neutralising F-spondin antibody on the anti-implantation effect of 2ME was explored. OR486 blocked the anti-implantation effect of E 2 ; 2ME, but not 4ME, affected embryo implantation. The 2ME concentration was increased after 0.5 and 1 h in plasma and 3 h in uterine fluid following E 2 treatment. 2ME increased levels of Spon1 at 12 and 24 h although F-spondin was increased at 12 h. F-spondin antibody blocked the effect of 2ME on embryo implantation. We conclude that 2ME impairs mouse embryo implantation via activation of F-spondin in the uterus. © 2019 CSIRO.